Game Model In Improving Agility In SLB C Students - Islahuddin, Mochamad Fahmi (Sains Global Institut, Indonesia, 2024)
This research aims to explore the relationship between game models and increasing the agility of students with special needs (SLB) type C. The research method used is qualitative with literature studies to collect information about game models that have been proven effective in increasing agility in children with special needs type C The research results show that the application of a game model that is structured and adapted to the needs of SLB C students can make a positive contribution to increasing their agility. The implication of this research is the importance of a creative and focused approach in developing game models to support the development of motor and agility skills in children with special needs.